A look at human scale development in Loma Linda in Soacha, Colombia: ideas for the implementation of a social office - Ardmirola-Mendoza, Catherine; Rodríguez-Giraldo, Jeimmy Andrea (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
This article is the result of the research entitled "Social Office of Social Work", whose purpose was to highlight the social, community, group and family needs and problems of the inhabitants of the Loma Linda neighborhood in the municipality of Soacha, four. Based on the Human Scale Development Approach presented by Max-Neef, Elizalde and Hopenhayn. For this, focus groups were applied, the results of which showed the importance of satisfying the needs of affection, participation, subsistence, understanding and protection in an interconnected way, which makes it possible to demonstrate the possibility of developing a proposal for a Social Office that carries out accompaniment processes for its satisfaction. This becomes a commitment to citizenship training on the identification of their problems, the recognition of their dignity and the articulation of efforts for the satisfaction of human needs, this goes through the individual, family, community and social scenarios.